Whole-genome assembly of Ganoderma leucocontextum (Ganodermataceae, Fungi) discovered from the Tibetan Plateau of China. Issue 12 (29th September 2021) - Liu, Yuanchao; Huang, Longhua; Hu, Huiping; Cai, Manjun; Liang, Xiaowei; Li, Xiangmin; Zhang, Zhi; Xie, Yizhen; Xiao, Chun; Chen, Shaodan; Chen, Diling; Yong, Tianqiao; et al.
Abstract: Ganoderma leucocontextum, a newly discovered species of Ganodermataceae in China, has diverse pharmacological activities. Ganoderma leucocontextum was widely cultivated in southwest China, but the systematic genetic study has been impeded by the lack of a reference genome. Herein, we present the first whole-genome assembly of G. leucocontextum based on the Illumina and Nanopore platform from high-quality DNA extracted from a monokaryon strain (DH-8). The generated genome was 50.05 Mb in size with an N50 scaffold size of 3.06 Mb, 78, 206 coding sequences, and 13, 390 putative genes. Genome completeness was assessed using the Benchmarking Universal Single-Copy Orthologs (BUSCO) tool, which identified 96.55% of the 280 Fungi BUSCO genes. Furthermore, differences in functional genes of secondary metabolites (terpenoids) were analyzed between G. leucocontextum and Ganoderma lucidum . Ganoderma leucocontextum has more genes related to terpenoids synthesis compared to G. lucidum, which may be one of the reasons why they exhibit different biological activities. This is the first genome assembly and annotation for G. leucocontextum, which would enrich the toolbox for biological and genetic studies in G. leucocontextum .